OPTIMALISASI DAN UJI EFEKTIVITAS ACTINOMYCETES PADA Brassica chinensis DI BAWAH CEKAMAN KEKERINGAN DAN pH MASAM ULTISOL - Dewi, Shendy Citra Oktaviana; Suprayogo, Didik; Rahmanto, Didi; Rini, Tri Setia (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Drought stress and acid soil pH are a form of abiotic stress on acid-dry land. Actinomycetes are a group of transitional microbes that have benefits as bioprotectants, biostimulators, and biofertilizers. This study aimed to determine the optimum growth environment for Actinomycetes at various incubation temperatures (25, 30, 35, and 40 ℃) and media pH (5, 6, 7, 8, and 9) and prove its effectiveness on mustard plants when given drought stress, and increase in acid soil pH. The research was conducted in the LOB greenhouse of PT Great Giant Pineapple using two factors, namely Actinomycetes (F22, F26, F34, F39, and F47) and irrigation (watered and not watered). Observations included Actinomycetes population (CFU mL-1), plant response (percentage of stress, death, survival, recovery), plant growth (plant length, number of leaves, root length), plant production (fresh weight), soil pH, and soil organic matter. Results of this study showed that Actinomycetes F22 gave the highest total population (107 CFU mL-1), and the P4K1, P4K2, and P2K2 treatment combination gave the best results on the observed parameters.